2021
DOI: 10.1097/fjc.0000000000001097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fasting on Cardiovascular Outcomes in Patients With Hypertension

Abstract: Fasting has been frequently practiced for religious or medical purposes worldwide. However, limited literature assesses the impact of different fasting patterns on the physiologic and cardiac-related parameters in patients with hypertension. This review aims to examine the effect of fasting on cardiovascular outcomes in hypertensive patients. Medline, Embase, and Cochrane library were systematically screened until March 2021 for observational prospective cohorts investigating the effect of fasting on cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, in a large clinical trial comparing intermittent fasting with reduced caloric intake versus a general calorie-restricted diet, both strategies were associated with reduced weight and BP, but there was no significant difference between the groups [ 206 ]. In a meta-analysis of 33 studies ( n = 3213), fasting was associated with lower BP at end of Ramadan compared with before Ramadan, among those with diabetes, normotension and hypertension but no change in BP in those with chronic kidney disease [ 207 ]. Further, there was no statistically significant increase in worsening renal outcomes associated with fasting [ 208 , 209 ].…”
Section: Intermittent Fastingmentioning
confidence: 99%
“…However, in a large clinical trial comparing intermittent fasting with reduced caloric intake versus a general calorie-restricted diet, both strategies were associated with reduced weight and BP, but there was no significant difference between the groups [ 206 ]. In a meta-analysis of 33 studies ( n = 3213), fasting was associated with lower BP at end of Ramadan compared with before Ramadan, among those with diabetes, normotension and hypertension but no change in BP in those with chronic kidney disease [ 207 ]. Further, there was no statistically significant increase in worsening renal outcomes associated with fasting [ 208 , 209 ].…”
Section: Intermittent Fastingmentioning
confidence: 99%
“…The effect of fasting on cardiovascular outcomes in hypertensive patients was reviewed in several major databases. 17 The review included studies assessing Ramadan, intermittent, and water-only fasting. Water-only fasting reduces body weight, BP, and lipolytic activity of fasting hypertensive patients without affecting the average heart rate.…”
Section: Impact Of Rf On Cardiovascular Disease and Risk Factorsmentioning
confidence: 99%
“…Despite the potential short-term benefits that accrue to the fasting person with hypertension, the evidence is weak when considering the long-term benefits on cardiovascular health, and consequently, there can be no claims to long-term cardio-protection. 19 We could find no reports of adverse effects of anti-hypertensive medications in individuals who were fasting. This was surprisingly true even when diuretics were assessed during the fasting period, though the single observational study that evaluated and reported on this had a relatively small sample size.…”
Section: Hypertensionmentioning
confidence: 97%